ANALISIS PERSEPSI PELAKU USAHA DI KOTA MEDAN TERHADAP RENCANA REDENOMINASI - Arif Hardiyanto; Murni Daulay (Ekonomi dan Keuangan, 2013)
Fractional currency that is too big an impact on inefficiencies in the payment system. Simplification of zeros on the currency makes transaction processing and accounting system simpler. Redenomination will not reduce purchasing power. Redenomination plan to do with the best possible plan of Bank Indonesia. Unpreparedness of the policy will have an impact on the economic turmoil and public panic. Socialization is very necessary because there are many people we do not understand the meaning of redenomination. Successful redenomination can be done when a country's economy is relatively stable.Keywords: Redenomination, Bank Of Indonesia.